Pengaruh Fluktuasi Suhu Penyimpanan Beku terhadap Perubahan Mutu Pre-baked Kroisan dan Produk Akhir - Akbar, Kelvin Muhammad; Suyatma, Nugraha Edhi; Nurtama, Budi (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Frozen pre-baked products are widely used in the bakery industry as they enhance productivity, ensure product availability, and expand distribution networks. One of the pastry products that incorporates pre-baked dough is the croissant. However, in practice, frozen storage facilities often experience temperature fluctuations, which can affect the quality of both pre-baked products and their final baked forms. Storage under unstable temperature conditions tends to cause greater product deterioration compared to storage at stable temperatures. This study aimed to compare the quality changes in pre-baked croissants (PBCr) and their final baked products due to temperature fluctuations during PBCr frozen storage. The research was conducted in a bakery industry setting (PT XYZ) by observing product characteristics after freezing (PBCr) and after baking. The observed parameters included weight, volume, and color intensity. Storage under fluctuating temperature conditions led to a significant decline in product quality (p